Methane emissions and growth rate of lambs fed Laminaria hyperborea supplemented diet - Lind, Vibeke; Hayes, Maria; Waters, Sinéad M.; Kirwan, Stuart F.; Aasen, Inga Marie (Frontiers in Animal Science, 2025)
IntroductionThe discovery of the methane-mitigating effect of the red seaweed Asparagopsis taxiformis has triggered a search for other seaweed species with similar effects. Brown seaweeds constitute the largest production volume of seaweeds in Europe. Some brown algae are known to inhibit methanogens and could potentially reduce enteric methane emissions. Use of by-products generated from industrial processing of plants are typically inedible for human consumption but well known as ruminant feeds. As fractions from Laminaria hyperborea showed significant reductions in methane emissions in vitro, a L. hyperborea by-product was chosen for an in vivo trial with sheep. The aim was to investigate the effect of L. hyperborea by-product inclusion in the diet of growing lambs on dry matter intake, methane emissions, growth rate and nitrogen digestibility. MethodsTwenty-four Norwegian White Sheep lambs (12 ewe and 12 male lambs, 4 months; 36.8 kg live weight) were fed a Control diet (grass silage and control concentrate) or an Algae diet (grass silage and algae concentrate 2% inclusion rate). Lambs were fed a basic diet (grass silage and neutral concentrate) and, in staggered order, introduced to their respective diets for five weeks before entering one of six open circuit respiration chambers. Methane production was measured for three consecutive days. All lambs entered the chambers three time (Periods 1, 2 and 3). Feed intake was measured four consecutive days a week, and live weight (kg) was measured every two weeks. Twelve male lambs were used to investigate in vivo nitrogen digestibility using metabolism crates.ResultsThe inclusion rate of L. hyperborea by-product was above the target and ended at 2.5% of DM. There was an increase in feed intake and live weight over the experimental period, consistent with the growth of the lambs. Methane production, yield, or intensity was not affected by diet, overall, but the Algae diet reduced methane in Period 1. Male lambs produced more methane than female lambs. Algae inclusion affected live weight negatively.DiscusssionIt is concluded that use of L. hyperborea by-products as a feed additive to sheep needs further investigation due to inconclusive results in the present study.